Identification of Worm Parasites in Beef Cattle Feces in the Village Nangka Bay, Kubu Raya District - Rohayeti, Yeti; Heraini, Dela; Subhi, Imam Mahdi Maulana (Fakultas Peternakan, Universitas Padjadjaran, 2024)
Beef cattle are meat-producing cattle used for fulfilling and improving people's nutrition. The increase in the beef cattle population in Indonesia has not fully met the demand for meat nationally due to the low productivity of local livestock. Low livestock productivity can occur due to livestock health factors, one of them being caused by worm parasites infection. This disease causes economic loss, resulting in lower growth and weight gain, and can lead to death. A qualitative examination, stool test is needed for a qualitative examination to identify gastrointestinal parasites in livestock, especially the type and degree of infection. This study aims to identify the types of worms found in the beef cattle faeces in Teluk Nangka Village, Kubu District. This study uses a quantitative descriptive method. The parameters used in this study were the identification of worm parasites in the faeces of beef cattle in Teluk Nangka Village, Kubu District. Examination of samples using the sedimentation method and the floating method. The research results show that the types of worm parasites found in beef cattle faeces in Teluk Nangka Village, Kubu District, Kubu Raya Regency are Strongyloides sp, Trichostrongylus sp, Moniezia sp and Taenia sp.